Expression, purification, and molecular characterization of plasmodium falciparum FK506-binding protein 35 (PfFKBP35) - Yoon, Hye Rim (2012)
The immunosuppressive drug FK506 binds its targets FK506-binding protein (FKBP) family and modulates cellular processes.